Tourism in the USA : a spatial and social synthesis - Ioannides, Dimitri, 1961- (Routledge, 2009)
Offers students a comprehensive overview of both tourism and travel in USA, focusing on the disciplines of Geography, Tourism Studies and, more generally, Social Science.